The relation between access to water poverty and patriarchy : the case of women slum dwellers in Kibera Kenya - Brand, Danie (Jacobus Frederick Daniel, 1968- ) (University of Pretoria, 2020)
Thesis (LLD)--University of Pretoria, 2019.